2009
DOI: 10.1159/000204763
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childhood Neglect with Adult Dissociation in Schizophrenic Inpatients

Abstract: Background: Dissociation is often related to previous trauma and also occurs frequently in schizophrenia. Dissociation and psychosis may reflect a posttraumatic syndrome in some patients with schizophrenia. Sampling and Methods: In total, 80 patients diagnosed with schizophrenia were investigated by means of the Childhood Trauma Questionnaire (CTQ), the Dissociative Experience Scale and the Symptom Check List 90-R. CTQ subscales and groups reporting high and low dissociation were compared using MANOVA. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 79 publications
4
26
1
3
Order By: Relevance
“…This is not surprising, as a growing amount of data report the association between CM and adult dissociative psychopathology. 16,[44][45][46][47][48][49] It has been suggested that the development of dissociation, reflecting severe deficits in the integration of the self, can be an outcome of CM, 50 and severity and chronicity of maltreatment have been found to predict future levels of dissociation. 51 In particular, a meta-analysis, evaluating 26 studies with 2108 subjects involved, reports a positive association between CM and dissociation regardless of the type of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as a growing amount of data report the association between CM and adult dissociative psychopathology. 16,[44][45][46][47][48][49] It has been suggested that the development of dissociation, reflecting severe deficits in the integration of the self, can be an outcome of CM, 50 and severity and chronicity of maltreatment have been found to predict future levels of dissociation. 51 In particular, a meta-analysis, evaluating 26 studies with 2108 subjects involved, reports a positive association between CM and dissociation regardless of the type of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Vogel et al (2006) found that even patients without a history of trauma or posttraumatic symptoms can elevate a level of dissociation on the DES scale and in a later study (Vogel et al, 2009b) it has been showed that dissociation has a more proximal impact on schizophrenia symptoms then trauma history. Moreover, a worse capability to discriminate negative emotion in schizophrenia and schizoafective patients is probably associated with amnestic dissociation and therefore with functional deficit in these disorders (Renard et al, 2012).…”
Section: Dissociation Splitting and Metacognitionmentioning
confidence: 96%
“…Moreover, a worse capability to discriminate negative emotion in schizophrenia and schizoafective patients is probably associated with amnestic dissociation and therefore with functional deficit in these disorders (Renard et al, 2012). All these recent findings show that dissociation is not only related to previous trauma history and that it may contribute to characteristic feature of schizophrenia, perhaps as a psychological mechanism of defense for mitigation of strong disorganizing affects or inner conflicts (Giese et al, 1997;Vogel et al, 2009b). But it seems that dissociation doesn't serve effectively in this way in psychoses.…”
Section: Dissociation Splitting and Metacognitionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, their study used the Childhood Trauma Questionnaire (CTQ) [13], which is known to have a limited ability to discriminate between abuse and neglect (see below). Using the same indicator, Vogel et al [14] found that physical neglect predicted dissociation in schizophrenics, while abuse did not. Moreover, Claussen and Crittenden [15] in 1991 found in their study that psychological maltreatment was more predictive of a child's developmental impairment than the severity of physical abuse.…”
Section: Introductionmentioning
confidence: 99%